Propuesta de una estructura de costos totales para RAC LOGISTIC S.A.S que permita establecer un valor de flete competitivo en el mercado. - Gutiérrez Rojas, Jonathan Daniel; Suárez Ríos, Eloísa Katerine (Universidad Antonio Nariño, 2025)
Efficiency and cost control are crucial for budget management, vital information for administrative decision-making in freight transportation companies. This study focuses on RAC LOGISTIC S.A.S, a company located in Bogotá, which has a fleet of 7 tractor-trailers with a capacity of 34 tons each. These vehicles transport various types of cargo to multiple destinations in Colombia.